Aktualisasi Kurikulum Terintegrasi di SMA Trensains Tebuireng Jombang - Kurroti A'yun; Wildanul Fajri; Sunardi Sunardi (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2018)
Quality education is produced from quality process. The superior graduates is produced from formation and development their character values which are internalized to be superior individuals. To produce graduates with values character needs effective planning, implementing, and supervision. This research discusses the concept of SMA Trensains Tebuireng curriculum such as; component, structure, and actualization of integrated curriculum, the steps of actualization of integrated curriculum, and the implication of curriculum. SMA Trensains Tebuireng implements Semesta curriculum which combines between national, international, and pesantren sains wisdom curriculum. And the actualization steps are planning, implementing, evaluating, and activity completeness, and measurability of results achieved.